AUTHOR’S IDENTIFICATION SYSTEMS AS AN INSTRUMENT FOR ENHANCING OF RESEARCH PUBLICATIONS VISIBILITY ON THE WEB - A. V. Skalaban; I. V. Yurik (Системный анализ и прикладная информатика)
The purpose of the article is to give the reader some information on some problems related to the correctness and completeness of the initial data in the measurement and evaluation of scientific activity by bibliometric methods using scientometric databases. The article gives a detailed analysis of the main systems of identification of the authors. Recommendations to address the identified problems and the promotion of authors in the world scientific information space are described in the article.